Selected Abstracts of the 1st Congress of joint European Neonatal Societies (jENS 2015); Budapest (Hungary); September 16-20, 2015; Session "Pharmacology" - - (Hygeia Press di Corridori Marinella, 2015)
Selected Abstracts of the 1st Congress of joint European Neonatal Societies (jENS 2015); Budapest (Hungary); September 16-20, 2015 ORGANIZING INSTITUTIONS European Society for Neonatology (ESN), European Society for Paediatric Research (ESPR), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI), with the local host of Hungarian Society of Perinatology and Obstetric Anesthesiology, Hungarian Society of Perinatology (MPT), supported by Council of International Neonatal Nurses (COINN), organizing secretariat MCA Scientific Events PROGRAMME COMMITTEE Artúr Beke (Hungarian Society), Morten Breindahl (ESN), Giuseppe Buonocore (UENPS), Pierre Gressens (ESPR), Silke Mader (EFCNI), Manuel Sánchez Luna (UENPS), Miklós Szabó (Hungarian Society of Perinatology), Luc Zimmermann (ESPR)   Session "Pharmacology" ABS 1. BABY SKIN CARE PRODUCTS • P. Doro, R. Abraham, D. Agoston, J. Balog, R.Z. Csoma ABS 2. MATHEMATICAL MODELING TO PREDICT IN-HOSPITAL NATURAL WEIGHT CHANGES IN TERM NEONATES • S. Kasser, M. Wilbaux, C. De Angelis, H. Rickenbacher, N. Klarer, J.N. Van Den Anker, M. Pfister, S. Wellmann ABS 3. IMPROVING PARENTERAL NUTRITION IN THE NEONATE - A PRACTICAL GUIDELINE • H. Reigstad, D. Moster, I. Grønlie, A. Blystad ABS 4. INVOLUTION OF RETINOPATHY OF PREMATURITY AND NEURODEVELOPMENTAL OUTCOME AFTER BEVACIZUMAB TREATMENT • Y.-S. Chang, P.-N. Tsao, C.-Y. Chen, H.-C. Chou, W.-S. Hsieh, P.-T. Yeh ABS 5. RELATIONSHIP BETWEEN ADVERSE DRUG REACTIONS AND OFF-LABEL/UNLICENSED DRUG USE IN HOSPITALISED CHILDREN. EREMI STUDY • K.A. Nguyen, Y. Mimouni, A. Lajoinie, N. Paret, S. Malik, L. El-Amrani, L. Milliat-Guittard, C. Carcel, A. Portefaix, A.M. Schott, T. Vial, B. Kassai ABS 6. A SYSTEMATIC REVIEW OF OFF-LABEL AND UNLICENSED DRUGS USE AND ADVERSE DRUG REACTIONS IN HOSPITALIZED CHILDREN • N. David, K.A. Nguyen, Y. Mimouni, A. Lajoinie, S. Malik, B. Kassai ABS 7. EFFICACY AND SAFETY OF PROPOFOL SEDATION FOR THE TREATMENT OF RETINOPATHY OF PREMATURITY IN SPONTANEOUS BREATHING • A. Di Pede, G. Catena, C. Auriti, I. Capolupo, S. Lozzi, S. Picardo, A. Dotta, S. Sgrò ABS 8. ELEVATED TROUGH SERUM GENTAMICIN CONCENTRATIONS AND OTOTOXICITY • K. Swamy, D. Jayasinghe, R. Smith ABS 9. RELATIONSHIP BETWEEN DOPAMINE INFUSION AND HEMODYNAMIC PARAMETERS IN PRETERM INFANTS • L.A.F. van Rossum, B. Riphagen, M. Lardinois, A.C.G. Egberts, F. van Bel, P.M.A. Lemmers ABS 10. DOPAMINE AND DOBUTAMINE: DOES TEMPERATURE OR INTRAVENOUS VEHICLE AFFECT STABILITY? • C. Thompson, L. Mahoney, G. Scutt, B.A. Patel, H. Rabe ABS 11. COMPARISON OF THE EARLY AND LATE CAFFEINE THERAPY ON CLINICAL OUTCOMES IN PRETERM NEONATES • R. Saeidi, S. Maghrebi ABS 12. COMPARISON OF ORAL IBUPROFEN AND INTRAVENOUS IBUPROFEN IN NEONATES WITH PATENT DUCTUS ARTERIOSUS IN A TERTIARY MEDICAL CENTER OF TAIWAN • W.C. Yang, C.Y. Chen, H.C. Chou, P.N. Tsao, W.S. Hsieh ABS 13. REDUCTION IN PRESCRIPTION ERRORS IN A NEONATAL INTENSIVE CARE UNIT: A COMPLETED AUDIT CYCLE • T. Fordham, H. Green, B. Qureshi, H. Ibrahim, N.V. Subhedar ABS 14. POTENTIALLY HARMFUL EXCIPIENTS IN MEDICINES PRESCRIBED IN NEONATAL INTENSIVE CARE UNITS (NICUs) - PRODUCT SUBSTITUTION AS A WAY FORWARD • G. Nellis, I. Lutsar, H. Varendi, M.A. Turner, T. Metsvaht ABS 15. NEPHROTOXICITY RELATED TO VANCOMYCIN AND AMIKACYN ASSOCIATION IN NEONATAL PATIENTS • R. Bianchi, M.L. Pequeno, H. Souza, B. Santin, J. Ropero, S. Salman, R. Mason, S. Taniguchi ABS 16. REVIEW OF SECOND LINE ANTIBIOTIC CHOICE ON A TERTIARY NEONATAL UNIT IN THE UNITED KINGDOM • L. Perkins, J. Matthes ABS 17. DOXAPRAM THERAPY IN NEWBORNS; SHOULD WE STILL USE IT? • R. Flint, N. Halbmeijer, I. Reiss, S. Simons ABS 18. VANCOMYCIN THERAPEUTIC DRUG MONITORING IN NEONATES: ARE THERE INTRA-ASSAY DIFFERENCES? • A. Smits, M. Oyaert, P. Vermeersch, V. Cossey, G. Naulaers, S. Pauwels, I. Spriet, K. Allegaert ABS 19. GENTAMICIN EXPOSURE AND SENSORINEURAL HEARING LOSS IN PRETERM INFANTS • A. Fuchs, L. Zimmermann, M. Bickle Graz, J. Cherpillod, J.-F. Tolsa, T. Buclin, E. Giannoni ABS 20. QUANTIFICATION OF THE IMPACT OF PHARMACOGENETICS ON TRAMADOL DISPOSITION IN EARLY INFANCY • K. Allegaert, R. van Schaik, V. Cossey, C. Vanhole, J. de Hoon, J. van den Anker, S. de Wildt ABS 21. PHARMACOKINETICS OF ANTENATAL MAGNESIUM SULFATE IN PRETERM INFANTS FOR NEUROPROTECTION • N. Merchant, A. Hawaa, A.D. Edwards, E. Mulder, J. Derks, K. Keunen, C. Sol, H. Hagberg, M. Benders ABS 22. DETERMINATION OF OPTIMAL DOSING OF RECOMBINANT HUMAN IGF-1/IGFBP-3 TO ESTABLISH AND MAINTAIN PHYSIOLOGICAL INTRAUTERINE SERUM IGF-1 LEVELS IN PRETERM INFANTS • B. Hallberg, I. Hansen-Pupp, J.-K. Chung, J. Sharma, G. Fetterly, M. Mascelli, N. Kreher, N. Barton, A. Hellström, D. Ley ABS 23. EARLY INTRAVENOUS PARACETAMOL CLOSES DUCTUS ARTERIOSUS IN VERY PREMATURE INFANTS: A RANDOMIZED, CONTROLLED TRIAL • P. Härkin, A. Härmä, O. Aikio, M. Valkama, M. Leskinen, T. Saarela, M. Hallman ABS 24. NEW PERSPECTIVES IN NEONATAL ANALGOSEDATION: DEXMEDETOMIDINE • F. De Rienzo, I. Demarchi, C. Fiorito, D. Sola, S. De Franco, I. Stasi, M.R. Gallina, F. Ferrero ABS 25. RISK ASSESSMENT BASED ON AN EXPERIMENTAL MODEL TO EVALUATE COMPATIBILITY OF RECOMBINANT IGF-1/IGFBP-3 WITH INTRAVENOUS MEDICATIONS COMMONLY ADMINISTERED IN THE NEONATAL ENVIRONMENT • M. Turner, A. Bandekar, N. Barton, T. Hsiao, E. Jochim, J. Knaack, N. Kreher, B. Mangum, C. McPherson, S. Tenjarla, N. Salamat-Miller